2005
DOI: 10.1289/ehp.7340
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence among Glyphosate-Exposed Pesticide Applicators in the Agricultural Health Study

Abstract: Glyphosate is a broad-spectrum herbicide that is one of the most frequently applied pesticides in the world. Although there has been little consistent evidence of genotoxicity or carcinogenicity from in vitro and animal studies, a few epidemiologic reports have indicated potential health effects of glyphosate. We evaluated associations between glyphosate exposure and cancer incidence in the Agricultural Health Study (AHS), a prospective cohort study of 57,311 licensed pesticide applicators in Iowa and North Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
264
0
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(277 citation statements)
references
References 47 publications
2
264
0
11
Order By: Relevance
“…Since then, however, some experimental studies indicate genotoxic, hormonal and enzymatic effect in mammals, as reviewed. 32 Of particular interest is that glyphosate treatment of human lymphocytes in vitro resulted in increased sister chromatid exchanges, 33 chromosomal aberrations and oxidative stress. 34,35 Odds ratios (OR) and 95% confidence intervals (CI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, however, some experimental studies indicate genotoxic, hormonal and enzymatic effect in mammals, as reviewed. 32 Of particular interest is that glyphosate treatment of human lymphocytes in vitro resulted in increased sister chromatid exchanges, 33 chromosomal aberrations and oxidative stress. 34,35 Odds ratios (OR) and 95% confidence intervals (CI).…”
Section: Discussionmentioning
confidence: 99%
“…36 Recent findings from other groups also associate glyphosate with different B-cell malignancies such as lymphomas and myeloma. 32,37,38 Glyphosate has succeeded MCPA as one of the most used herbicides in agriculture, and many individuals that used MCPA earlier are now also exposed to glyphosate. This probably explains why the multivariate analysis does not show any significant ORs for these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports from the Agricultural Health Study, evaluating glyphosate (n 5 57,311 applicators), pendimethalin (n 5 24,374 applicators), metolachlor (n 5 50,193 applicators), diazinon (n 5 23,106 applicators), alachlor (n 5 26,510 applicators), chlorpyrifos (n 5 54,383 applicators), atrazine (n 5 36,513 applicators), and carbofuran (n 5 49,877 applicators) exposure, found no significant exposure-response gradients in NHL risk based on lifetime or intensity-weighted days of exposure. [41][42][43][44][45][46] Furthermore, there were no significant associations with any of these chemicals, based on comparing the incidence of NHL in the highest category of cumulative lifetime exposure to the lowest (atrazine RR 5 1.61, 95% CI: 0.62-4.16, p for trend 5 0.35; 48 alachlor RR 5 1.14, 41 ).…”
Section: Occupational and Environmental Factors Occupational And Envimentioning
confidence: 98%
“…From a human health perspective, glyphosate is classified as carcinogenic category E because of evidence of noncarcinogenicity for humans [21]. Some studies have suggested a link between glyphosate exposure and the risk of non-Hodgkin's lymphoma or human placental cell damage [22,23].…”
Section: Introductionmentioning
confidence: 99%